2022
DOI: 10.2217/3dp-2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

The use of 3D-Printed Models in Patient Communication: A Scoping Review

Abstract: 3D models have been used as an asset in many clinical applications and a variety of disciplines, and yet the available literature studying the use of 3D models in communication is limited. This scoping review has been conducted to draw conclusions on the current evidence and learn from previous studies, using this knowledge to inform future work. Our search strategy revealed 269 papers, 19 of which were selected for final inclusion and analysis. When assessing the use of 3D models in doctor–patient communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Other investigators have also found 3D models to improve communication quality and efficiency with patients, especially those with relatively poor anatomical knowledge 42 , 54 58 A review by Traynor et al. 59 found that limited studies looked at using 3D models during consultations and no studies looked at how 3D models could be used in communication between patients and families and their friends. Studies using patient-specific 3D printed models in paediatric consultations typically focus on the parent perspective only.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have also found 3D models to improve communication quality and efficiency with patients, especially those with relatively poor anatomical knowledge 42 , 54 58 A review by Traynor et al. 59 found that limited studies looked at using 3D models during consultations and no studies looked at how 3D models could be used in communication between patients and families and their friends. Studies using patient-specific 3D printed models in paediatric consultations typically focus on the parent perspective only.…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to use relationship-based communication skills to engage and spend time with the parents, establish an empathetic relationship with them to modify their behavior, educate them, enlist their help, and make them partners in treatment of their child [63][64][65]. It has been shown that 3D-printed models may help to improve physician-patient communication [66]. However, these are expensive, and it may not be easily available for facilities to develop these models in low-to-middle-income countries.…”
Section: Errors During the Bracing Phasementioning
confidence: 99%
“…The role of using 3D printed models in enhancing doctor-patient communication has been reported in the literature, although only a limited number of studies are available, according to a recent scoping review. Traynor et al conducted a comprehensive review of the current literature and identified 19 studies on the use of 3D printing in patient communication [ 71 ]. Of these studies, seven studies were related to cardiology and cardiovascular surgery [ 49 , 72 , 73 , 74 , 75 , 76 , 77 ], of which four studies were reported from the same research group [ 72 , 73 , 74 , 75 ].…”
Section: Clinical Applications Of 3d Printed Models In Cardiovascular...mentioning
confidence: 99%